British-Bangladeshi women in higher education : aspirations, inequities and identities - Scandone, Berenice (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Drawing on primary qualitative research, this book explores the experiences and identities of a group of British-born women of Bangladeshi background attending university in London through a Bourdieusian theoretical framework. It demonstrates the inequities that these women experience in UK higher education and employment as well as how they challenge them. This book presents stories that illuminate the diversity of views and experiences marked by dynamics of class, race, ethnicity, religion and gender. These stories reveal family projects of social mobility and discourses of aspiration, the multiple resources and constraints that influence decisions, experiences and pathways, and the mutual construction of different dimensions of identification and tensions between them. Through participants' narratives, the book tackles wider questions around fair access to education and employment, social mobility and the (re)production and transformation of social inequities. The book will be of interest to scholars and students in the fields of Youth, Education, Race/Ethnicity and Migration Sociology, as well as community and education practitioners and anyone with an interest in multi-ethnic societies and young people's histories"--
Introduction -- Bourdieu, social change and intersectionality -- Career aspirations, expectations and pathways -- 'It's one of the norms of our culture': Diasporic discourses of valuing education -- University decision-making and experiences -- Social class and ethnic identification -- Conclusions.
Keywords: Bangladeshis -- Education (Higher) -- Great Britain -- Case studies; Muslim women -- Education (Higher) -- Great Britain -- Case studies; Discrimination in education -- Great Britain; Discrimination in employment -- Great Britain; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Women's Studies